Christian Ethics Education as a Solution for the Problem of Online Gambling and Online Loans in Christian Societies - Pariama, Leonardo Stevy; Patty, Junus Paulus; Sipakoly, Selly; Litamahuputty , Jacomina Vonny (PT. BATARI EDU CALYA, 2024)
The rise of online gambling presents significant ethical and social challenges, particularly within Christian communities, where such behavior conflicts with core religious values. This study examines the potential of Christian ethics education as a solution to mitigate the impact of online gambling, highlighting principles of stewardship, self-control, and moral integrity as key frameworks for addressing this issue. Through a qualitative descriptive approach based on literature review, this research explores the addictive nature of online gambling, its effects on individuals and families, and the Christian perspective on gambling-related behaviors. Findings suggest that Christian ethics education can play a crucial role in fostering awareness and resilience against gambling addiction, promoting values that align with responsible living, financial prudence, and community harmony. This study underscores the importance of integrating Christian ethical teachings into community and church programs as a preventive strategy, offering believers practical guidance to navigate the moral challenges of the digital age.